2018
DOI: 10.1002/jcp.26615
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of miR378* on doxorubicin‐induced cardiomyocyte injury via calumenin

Abstract: Doxorubicin (Dox) is a highly effective antitumor antibiotic, however myocardial toxicity severely limits its use clinically. The pathogenesis of doxorubicin‐induced cardiomyopathy is unclear. In Dox cardiomyopathy mice, there is a decline in cardiac function, a change in myocardial pathology and a reduction in miR378* expression. Expression changes in calumenin, an endoplasmic reticulum stress (ERS) chaperone protein and pathway factor, as well as apoptosis, were observed in cardiomyocytes after doxorubicin‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Some studies have reported that ERS and autophagy play a role in the internal regulatory mechanism, Chen et al ( 31 ) reported that isodunnianol reduced myocardial damage caused by doxorubicin by activating protective autophagy, whereas Fu et al ( 32 ) reported that chemical endoplasmic reticulum chaperone molecules can alleviate Dox-induced cardiac dysfunction. miR378 alleviates ERS and inhibits activation of the ERS-mediated apoptosis signaling pathway in cardiomyocytes via regulating calumenin expression, thereby reducing cardiomyocyte apoptosis after doxorubicin-induced injury ( 33 ). Another study reported that doxorubicin blocks autophagic flux in cardiomyocytes by impairing lysosome acidification and lysosomal function.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that ERS and autophagy play a role in the internal regulatory mechanism, Chen et al ( 31 ) reported that isodunnianol reduced myocardial damage caused by doxorubicin by activating protective autophagy, whereas Fu et al ( 32 ) reported that chemical endoplasmic reticulum chaperone molecules can alleviate Dox-induced cardiac dysfunction. miR378 alleviates ERS and inhibits activation of the ERS-mediated apoptosis signaling pathway in cardiomyocytes via regulating calumenin expression, thereby reducing cardiomyocyte apoptosis after doxorubicin-induced injury ( 33 ). Another study reported that doxorubicin blocks autophagic flux in cardiomyocytes by impairing lysosome acidification and lysosomal function.…”
Section: Discussionmentioning
confidence: 99%
“…CALU, a calcium-binding protein localized in the endoplasmic reticulum (ER), is mainly involved in such ER functions as protein folding and sorting. Besides, CALU has recently been shown to influence cell mobility, migration, invasion, and metastasis during particular events, such as tumorigenesis, wound healing, immune response, and coagulation [ 16 , 17 , 18 , 19 , 20 , 21 ]. Several studies have explored the relationship between CALU expression and survival and yielded relatively consistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Calumenin was described to be secreted in the surrounding medium [ 9 ]. It has been widely evaluated in various cancers by influencing tumorigenesis and therapeutic response [ 10 ]. Increased expression of calumenin was associated with poorer outcome in gliomas [ 11 ].…”
Section: Discussionmentioning
confidence: 99%